Morphological plasticity in response to salinity change in the euryhaline diatom Pleurosira laevis (Bacillariophyta). Issue 5 (30th July 2022) - Kamakura, Shiho; Ashworth, Matt P.; Yamada, Kazumasa; Mikami, Daichi; Kobayashi, Atsushi; Idei, Masahiko; Sato, Shinya
Abstract : Pleurosira laevis is a salt‐tolerant diatom distributed around the world. The valve of P. laevis has distinct structures called ocelli, which are sharply defined areas with fine, densely packed pores. Two formae of this diatom, P. laevis f. laevis and P. laevis f. polymorpha, are distinguished from each other by their flat or dome‐shaped valve faces and degree of elevation of the ocelli, respectively. In this study, we established 4 strains of P. laevis isolated from freshwaters or coastal areas in Japan and the United States, and tracked the formation of newly formed valves with the fluorescent SDV‐specific dye PDMPO in culture under several salinity conditions. The result clearly demonstrated the morphological plasticity of the valves, controlled by environmental salinity. The laevis form and polymorpha form valves were produced at salinities of 2 and 7, respectively. The salinity thresholds dictating the morphological plasticity of the valve were consistent in all 4 strains. A similar morphology to the polymorpha form was reproduced in a freshwater medium with the addition of sorbitol, suggesting that osmotic pressure plays a key role in this morphological plasticity. The highly reproducible and easily manipulated change in morphology makes this diatom an ideal model for lab experiments focusing on the molecular and genetic factors involved with valve morphogenesis.